Market Effeciency And Integration Analisys of Organic Vegetables In Medan - Sibuea, Muhammad Buhari (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
The study aims to analyze about marketing chain of organic vegetables, margin trading system and level...